2013
DOI: 10.1007/s11999-013-3062-z
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Injury Predicts Subsequent Function in Surgically Treated Displaced Intraarticular Calcaneal Fractures

Abstract: We found the severity of a DIACF related to subsequent foot function and quality of life. Both fracture severity classifications predicted function. Anatomic reconstruction of the shape and articular surfaces of the calcaneus leads to predictable function in the medium to long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 51 publications
2
38
0
7
Order By: Relevance
“…1,11,12,24,26,[27][28][29][30] When performing open reduction and internal fixation of DIACFs, anatomic reduction of overall shape of the calcaneus and meticulous restoration of subtalar joint congruity is prerequisites for reliable long-term results. [3][4][5][6][7]11,26 The most widely used extended lateral approach allows adequate exposure for anatomic reduction of the posterior, medial, and cuboidal facet, restoration of the lateral wall, and application of a locking or nonlocking plate. 9,12,24,31 A major concern when using extensile approaches is the development of soft tissue complications including hematoma, skin necrosis, soft tissue infection, and even osteitis of the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,11,12,24,26,[27][28][29][30] When performing open reduction and internal fixation of DIACFs, anatomic reduction of overall shape of the calcaneus and meticulous restoration of subtalar joint congruity is prerequisites for reliable long-term results. [3][4][5][6][7]11,26 The most widely used extended lateral approach allows adequate exposure for anatomic reduction of the posterior, medial, and cuboidal facet, restoration of the lateral wall, and application of a locking or nonlocking plate. 9,12,24,31 A major concern when using extensile approaches is the development of soft tissue complications including hematoma, skin necrosis, soft tissue infection, and even osteitis of the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, published studies on open reduction and internal fixation of DIACFs with a plate using an extensile lateral approach showed reproducibly good long-term results, provided proper reduction of the calcaneal shape and joint congruity. [3][4][5][6][7] However, soft tissue complications including hematoma, skin necrosis, soft tissue infection, and even osteitis of the calcaneus have been reported in up to 25% using extensile approaches. 1,6,[8][9][10][11][12] Therefore, alternative procedures including arthroscopically or fluoroscopically assisted percutaneous reduction and fixation, external fixation, and limited lateral or sinus tarsi approaches have been recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rammelt et al [23] reported that fracture severity has a predictive value for functional outcome. Csizy et al [24] showed that initial injury severity is the most predictive factor for late subtalar fusion.…”
Section: Primary Subtalar Fusionmentioning
confidence: 99%
“…The incidence of a wound infection following operative treatment of closed calcaneal fractures varies between 2 % and 25 % and rates of complications requiring surgery are up to 21 % [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%